Tēmpāvaṇit tiraṉ : collection of special lectures on Tempāvani - Iṉṉāci, C., 1934- (Āyvu Maiyam, Tamiḻ Mutukalaittuṟai, Tūya Cavēriyār Kallūri : Viṟpaṉai urimai, Vaḷaṉaruḷ Veḷiyīṭu, 1983)
Critical study of Tēmpāvaṇi, extended narrative poem on Jesus Christ, by Constantino Giuseppe Beschi, 1680-1747, Italian Jesuit missionary.